Action of Inhibitors of RNA and Protein Synthesis on Cell Enlargement - Noodén, Larry D. (1966)
Further studies with inhibitors of protein synthesis are presented to support the conclusion, drawn from work with chloramphenicol, that protein synthesis is a critical limiting factor in auxin-induced cell expansion. The indoleacetic acid-induced elongation of oat coleoptile sections was strongly inhibited by dl-p-fluorophenylalanine, and the inhibition is antagonized by phenylalanine. Puromycin at 10(−4) m very strongly inhibited the indoleacetic acid-induced growth of oat coleoptile and artichoke tuber sections and exerted a less powerful effect on pea stem sections. As found earlier with chloramphenicol, concentrations of puromycin effective in inhibiting the growth of coleoptile sections had quantitatively similar effects on protein synthesis, as measured by the incorporation of C(14)-leucine into protein of the coleoptile tissue. Several analogues of RNA bases were also tested, but while 8-azaguanine very strongly inhibited growth of artichoke tuber disks, 6-azauracil was the only one of this group clearly inhibitory to growth in coleoptile or pea stem sections. Actinomycin D actively inhibited both elongation and the incorporation of C(14)-leucine into protein in oat coleoptile sections. Inhibition of the 2 processes went closely parallel. Actinomycin D also powerfully inhibited growth of artichoke tuber disks. All the compounds effective in inhibiting growth generally inhibited the uptake of leucine as well. The possibility that auxin causes cell enlargement in plants by inducing the synthesis of a messenger RNA and of one or more new but unstable enzymes, is discussed. Possible but less favored alternative explanations are: A) that auxin induces synthesis of a wall protein, or B) that the continued synthesis of some other unstable protein (by a process independent of auxin) may be a prerequisite for cell enlargement.